Description and analysis of personal knowledge management skills among the staff of Ferdowsi University of Mashhad - Hajar Roohbakhsh; Rezvan Hossein Gholizade; Tahere javidi kalate jafar abadi (Iranian Journal of Information Processing & Management, 2017)
The main objective of this study is to describe and analyze personal knowledge management skills among staff of Ferdowsi University of Mashhad. To achieve this goal, the case study research  was used. The study population included all the staff which is permanent post formed expert, which means all the staff except the faculty staff of Ferdowsi University of Mashhad. Data collection was performed in two stages. First, in order to describe the amount of having the personal knowledge management skills of the staff of the Ferdowsi University of Mashhad, 137 experts of university were chosen for study. At this stage in order to collect data, the questionnaire of personal knowledge management skills Avery et al (2001) was used. The results of the quantitative data analysis showed that the experts at the University of Mashhad have an appropriate                 information in the personal management skills. In the second stage, to identify activities focused on each individual's knowledge management skills, the semi-structured interviews were used. The main number of informants at this stage of research consisted of sixteen permanent experts of Ferdowsi University of Mashhad. Based on the findings of qualitative data analysis at this stage, The most important activities related to personal knowledge management skills are: data recovery (data collection and schooling and gain information, ask, etc.), evaluation of information (recognize of good bases, evaluation of information, Check information proportion with the needs, etc.), Organizing information (prioritize, mentally planning, writing the key words, etc.), the sharing of knowledge and information (identification and problem solving, communicating with colleagues, adopt practices, etc.), Data analysis (analysis of information, use of information), the dissemination of knowledge and information (data exchange, information, putting information at the disposal of clients, etc.), security information (security information, supporting the information, annual Archives, etc.).